Hospitality Training Bagi Para Pengelola Homestay di Desa Liang Ndara Kabupaten Manggarai Barat - Gregorius A Berybe; Elisabet Oktaviani Hanggu; Maria Br Welalangi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2021)
Hospitality Training for Homestay Managers in Liang Ndara Village, West Manggarai Regency. This community service activity aims to increase the capacity of the Human Resources (HR) manager of the homestay in Liang Ndara Village, West Manggarai Regency. This service activity includes training related to sanitation and hygiene, food and beverage products, public speaking, and English language training. The method used in this activity is an educational method, which includes socialization, training, and assistance as a means of transferring knowledge and education for empowering homestay managers in Liang Ndara Village. This activity resulted in rapid progress for homestay managers, especially an understanding of sanitation and hygiene, food and beverage products, public speaking, and English. Homestay managers are ready to apply the knowledge they have gained to improve the quality of service at the homestay